Microbial exploration from two different ecosystems in Central Sulawesi, Indonesia - RATNAWATI RATNAWATI; SRI SUDEWI; KASMAN JAYA; ABDUL RAHIM SALEH (Society for Indonesian Biodiversity, 2022)
Abstract. Ratnawati, Sudewi S, Jaya K, Saleh AR. 2022. Microbial exploration from two different ecosystems in Central Sulawesi, Indonesia. Biodiversitas 23: 6191-6198. A supportive growing environment and the presence of microbes in the soil are considered good habitats for plant growth. Endophytic microbes live in symbiosis (mutual benefit) with their host plants, both in the stem and root tissues of plants, providing defense services in biotic and abiotic stress situations. This study was aimed to identify various microbes that exist in various agricultural cultivation ecosystems in Central Sulawesi. Microbial sampling was obtained from healthy plant tissues (endophytes) and rhizosphere in lowland rice and shallot plantation ecosystems. The sample obtained was then weighed as much as 5 g and surface sterilized for further isolation by serial dilution method to be spread on NA (Nutrient Agar) media for bacteria, and PDA (Potato Dextrose Agar) for fungi. The microbes that had grown were re-isolated to obtain pure isolate culture of microbes. The results showed that 8 isolates from the rhizosphere and 4 isolates as endophytes in the ecosystem of organic rice fields were recorded. The fungal isolates from the shallot plantation “Lembah Palu” found as many as 12 isolates from rhizosphere and 4 isolates as endophytes. The results of macroscopic and microscopic characteristics on fungal isolates identified as the species of Trichoderma, Fusarium, Penicillium, Gliocladium and Aspergillus.